2023
DOI: 10.24843/bulvet.2023.v15.i02.p17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi dan Identifikasi Ektoparasit pada Anjing Kintamani Bali di Bali

Abstract: Ektoparasit merupakan parasit yang hidup secara parasitik di bagian luar tubuh hospesnya atau terowongan didalam kulit yang masih berhubungan dengan lingkungan luar. Dampak yang ditimbulkan oleh infestasi ektoparasit pada anjing antara lain penurunan bobot badan, penurunan produksi, kerontokan rambut, iritasi, anemia sampai dengan kematian. Tujuan penelitian ini adalah untuk mengetahui prevalensi infestasi dan identifikasi ektoparasit yang menginfestasi Anjing Kintamani Bali (AKB). Sampel AKB yang digunakan be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…Based on research conducted by Ziemer et al, (2010), stated that there was a protozoan parasite infects swines. This research supported by the results obtained by Agustina et al, (2016) from 250 samples of piglet feces taken from farms in Bali province, it was known to be infected with protozoa with a prevalence of 91.6%. Protozoa that infect, among others, Amoeba sp.…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…Based on research conducted by Ziemer et al, (2010), stated that there was a protozoan parasite infects swines. This research supported by the results obtained by Agustina et al, (2016) from 250 samples of piglet feces taken from farms in Bali province, it was known to be infected with protozoa with a prevalence of 91.6%. Protozoa that infect, among others, Amoeba sp.…”
Section: Introductionsupporting
confidence: 79%
“…Research by Yuliasari et al (2013) in the Baliem Valley, which shows a prevalence of 10%. However, the results of the examination also showed a lower prevalence when compared to the study conducted by Agustina et al (2016), the results of the study conducted in traditional market in Bali showed a prevalence of 61.2%. Higher prevalence of Balantidium sp.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations